Traffic planning using geo-processing techniques - Sim, Nyap Fong. (2009)
Transportation demand modelling is one of the most important area in traffic planning. Hitherto, most transportation models have not found their way into GIS solutions. This slow development is attributed to the generic nature of GIS applications which are not ideally suited for very specific traffic demand modelling. However, more powerful computers and spatial processing methods will definitely lead to more effective use of GIS for transportation needs. Every specific traffic modelling application tends to have it unique needs associated with data and analysis procedures.